SISTEM MANAJEMEN PERPUSTAKAAN DALAM MENDUKUNG IMPLEMENTASI GERAKAN LITERASI SEKOLAH - Rusmini, Rusmini; Yusria, Yusria; Akhyar, Yundri (STKIP Pesisir Selatan, 2025)
This research examines the function of library management systems in facilitating digital literacy programs at MTs/MA Al-Kifayah Riau. The study seeks to elucidate the role of planning, implementation, and evaluation processes in the efficacy of digital literacy programs. A qualitative descriptive methodology was utilized, with data gathered via interviews, observations, and documentation involving librarians, educators, students, and school administrators. The results indicate that the library successfully incorporates digital technology into its services, consistent with the school's vision and mission. The planning phase emphasizes the development of programs aligned with the school's work plan (RKM), the enhancement of human resources via training, and the improvement of facilities to facilitate digital services. The implementation employs three methodologies: classroom-based literacy incorporating digital tools into education; school culture-based literacy utilizing digital collections and social media advocacy; and community-based literacy through partnerships with external stakeholders. Evaluation encompasses performance assessments, program outcome analysis, and recommendations for continuous improvement. Significant accomplishments encompass 80% digitalization, a substantial digital book repository comprising 2,762 titles, contemporary amenities such as electronic catalogs and multimedia corners, and pioneering Android-based services.